Notes on the early history of the Royal Regiment of Artillery - Cleaveland, Colonel (The Naval and Military Press ; Firepower The Royal Artillery Museum ; Andrews UK, 2012)
An unusual official manual setting out the history and duties of the Royal Regiment of Artillery from its formation down to 1757. The book provides a wealth of information on the orders, ordnance, duties and requirements of those who served ...